Investigation of 1-dimensional analysis for two-stroke spark ignition (SI) engine - Zabidi , Mohamad (2008)
The project is based on two-stroke engine. The two-stroke engine will be used as the testing engine that the performances can be determined. The objective of this project is to investigate and analysis the performance of two-stroke engine using a 1-Dimensional (engine gas dynamic) software. From this objective, the outcome of the project can be determined by using the 1-Dimensional software. The outcomes that need to be determined from this project are the performances of the engine. The 1-Dimensional software that was using in this project is GT-Power. GT-Power is using to model and simulate the two-stroke engine. First, the parameters of the two-stroke engine had been measured and then the modeling of the two-stroke engine had been built and simulated. After simulation process, the performances of the engines can be obtained right away. There are many information that can be taken from the GT-Power after simulating the engine but for analyzing, only several data had been chosen. Those data are pressure for scavenged port, in-cylinder and exhaust port, temperature for scavenged port, in-cylinder and exhaust port, brake power, brake torque, indicated mean effective pressure and brake specific fuel consumption. All of this information had been analyzed and the optimum engine speed had been determined at 1500 RPM to 2500 RPM because in this range, the brake torque and brake power is maximum while the brake specific fuel consumption also low.